A Study on a Method of Detecting Heavy Metal Content Using Thioglycolic Acid and Quartz Crucible - Fu, Guoqiang; Qian, Xinyue; Liu, Xinyi; Wang, Enxu (International Journal of Agriculture and Food Sciences Research, 2024)
In the Chinese Pharmacopoeia, the method of detecting heavy metals commonly uses thioglycolic acid. It is often used as a special method for the limit check of heavy metals in raw pharmaceutical or cosmetic raw materials. Traditional use of porcelain crucibles in sample pretreatment may result in false positive reactions. This study used quartz crucibles to replace the traditional porcelain crucibles to study the possibility of contamination. It was found that the false negative reactions caused by crucible material can be eliminated, and the precision of the method was verified by detecting three batches of samples. The method has good repeatability and accuracy. It can replace the use of traditional porcelain crucibles in the method of detecting heavy metals with thioglycolic acid.